Identification of signatory secondary metabolites during mycoparasitism of Rhizoctonia solani by Stachybotrys elegans - Chamoun, Rony; Aliferis, Konstantinos A.; Jabaji, Suha (Frontiers in Microbiology, 2015)
Stachybotrys elegans is able to parasitize the fungal plant pathogen Rhizoctonia solani AG-3 following a complex and intimate interaction, which, among others, includes the production of cell wall-degrading enzymes, intracellular colonization, and expression of pathogenic process encoding genes. However, information on the metabolome level is non-existent during mycoparasitism. Here, we performed a direct-infusion mass spectrometry (DIMS) metabolomics analysis using an LTQ Orbitrap analyzer in order to detect changes in the profiles of induced secondary metabolites of both partners during this mycoparasitic interaction four and five days following its establishment. The diketopiperazine(s) (DKPs) cyclo(S-Pro-S-Leu)/cyclo(S-Pro-S-Ile), ethyl 2-phenylacetate, and 3-nitro-4-hydroxybenzoic acid were detected as the primary response of Rhizoctonia four days following dual-culturing with Stachybotrys, whereas only the latter metabolite was up-regulated one day later. On the other hand, trichothecenes and atranones were mycoparasite-derived metabolites identified during mycoparasitism four and five days following dual-culturing. All the above secondary metabolites are known to exhibit bioactivity, including fungitoxicity, and represent key elements that determine the outcome of the interaction being studied. Results could be further exploited in programs for the evaluation of the bioactivity of these metabolites per se or their chemical analogues, and/or genetic engineering programs to obtain more efficient mycoparasite strains with improved efficacy and toxicological profiles.